Rare Germline DICER1 Variants in Pediatric Patients With Cushing's Disease: What Is Their Role? - Martínez de LaPiscina, Idoia; Hernández-Ramírez, Laura C.; Portillo, Nancy; Gómez-Gila, Ana L.; Urrutia, Inés; Martínez-Salazar, Rosa; García-Castaño, Alejandro; Aguayo, Aníbal; Rica, Itxaso; Gaztambide, Sonia; Faucz, Fabio R.; Keil, Margaret F.; et al. (Frontiers in Endocrinology, 2020)
Context: The DICER1 syndrome is a multiple neoplasia disorder caused by germline mutations in the DICER1 gene. In DICER1 patients, aggressive congenital pituitary tumors lead to neonatal Cushing’s disease (CD). The role of DICER1 in other corticotropinomas, however, remains unknown. Objective: To perform a comprehensive screening for DICER1 variants in a large cohort of CD patients, and to analyze their possible contribution to the phenotype. Design, setting, patients and interventions: We included 192 CD cases: ten young-onset (age <30 years at diagnosis) patients were studied using a next generation sequencing panel, and 182 patients (170 pediatric and 12 adults) were screened via whole-exome sequencing. In seven cases, tumor samples were analyzed by Sanger sequencing. Results: Rare germline DICER1 variants were found in seven pediatric patients with no other known disease-associated germline defects or somatic DICER1 second hits. By immunohistochemistry, DICER1 showed nuclear localization in 5/6 patients. Variant transmission from one of the parents was confirmed in 5/7 cases. One patient had a multinodular goiter; another had a family history of melanoma; no other patients had a history of neoplasms. Conclusions: Our findings suggest that DICER1 gene variants may contribute to the pathogenesis of nonsyndromic corticotropinomas. Clarifying whether DICER1 loss-of-function is disease-causative or a mere disease modifier in this setting, requires further studies.